2016
DOI: 10.3168/jds.2015-10433
|View full text |Cite
|
Sign up to set email alerts
|

Alternative haplotype construction methods for genomic evaluation

Abstract: Genomic evaluation methods today use single nucleotide polymorphism (SNP) as genomic markers to trace quantitative trait loci (QTL). Today most genomic prediction procedures use biallelic SNP markers. However, SNP can be combined into short, multiallelic haplotypes that can improve genomic prediction due to higher linkage disequilibrium between the haplotypes and the linked QTL. The aim of this study was to develop a method to identify the haplotypes, which can be expected to be superior in genomic evaluation,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
31
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(32 citation statements)
references
References 16 publications
0
31
0
1
Order By: Relevance
“…Some studies that tested other livestock populations reported that haplotypes can be advantageous for genomic prediction. Applying haplotype to genomic prediction has been studied in Montbeliarde bulls (Jónás et al, 2016), New Zealand dairy cattle (Hess et al, 2017), Nordic Holstein (Cuyabano et al, 2014;Cuyabano et al, 2015), and Danish Holstein bulls (Edriss et al, 2013). Although different haplotypes were used in these studies and the design of the studies may differ, their study still shows the benefits of using haplotype for genomic prediction.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies that tested other livestock populations reported that haplotypes can be advantageous for genomic prediction. Applying haplotype to genomic prediction has been studied in Montbeliarde bulls (Jónás et al, 2016), New Zealand dairy cattle (Hess et al, 2017), Nordic Holstein (Cuyabano et al, 2014;Cuyabano et al, 2015), and Danish Holstein bulls (Edriss et al, 2013). Although different haplotypes were used in these studies and the design of the studies may differ, their study still shows the benefits of using haplotype for genomic prediction.…”
Section: Discussionmentioning
confidence: 99%
“…As expected, the lower average |D'| value in the breeding population reflects its recombination history. The synthetic and the biparental population If there is higher LD between QTLs and haplotypes than with individual SNPs, haplotype blocks can provide substantial statistical power in association studies [6] and increased accuracy of genomic prediction of complex traits [36]. Surprisingly, our results evidenced that the number and length of the haplotype blocks and the number of SNPs per haplotype block were proportional to the average r 2 .…”
Section: Discussionmentioning
confidence: 67%
“…The construction of haplotypes at a particular SNP position by merging this SNP with the flanking markers is straightforward. However, due to the short distance between the markers, most of the resulting haplotypes included a small number of over-represented alleles together with a large number of alleles with low frequencies within the population (Jónás et al, 2016). It is expected that there is an optimal haplotype length, which depends on the distance between the markers and extent of LD in the population.…”
Section: Discussionmentioning
confidence: 99%